Error Analysis in Consecutive Interpreting by Interpreting Students - Muhammad Afif Musthofa (Jurnal Linguistik Terapan, 2025)
This study analyzed the errors demonstrated by students in a consecutive interpreting course at the Master’s Program in Linguistics at Universitas Brawijaya, explaining common issues and suggesting ways to promote better training. We adopted a qualitative approach that involved an analysis of 28 utterances from recorded videos of interpreting practice. The results indicated that 18 errors occurred in four main categories: inadequate language proficiency, distortion, omission, and non-conservation of paralinguistic elements. No literal translation errors were observed, indicating that the training was probably biased toward positive learning of the translation of context. However, the frequent errors made by the student interpreter showed that training is needed to overcome these issues. The recommendations include focusing on vocabulary development, practices that develop real-time usage and speech fluency, and cognitive load and/or anxiety training. These findings can be useful for future research in consecutive interpreting error analysis and in designing comprehensive training frameworks toward professionalism among novice interpreters.